1982
DOI: 10.1111/j.1365-2621.1982.tb12881.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Restructured Beef/Pork Steaks

Abstract: The effects of added antioxidants on restructured combination (5050) beef-pork steaks were studied. Steaks were formulated to contain 20% fat and 0.75% salt. Antioxidants used at a 0.02% level (based on fat content of meat) were butylated hydroxyanisole (BHA), tertiary butyl hydroquinone (TBHQ), and a combination of BHA and TBHQ. Cooked steaks were evaluated for sensory properties and overall acceptability, initially and after 4, 8, 12, 16, an 20 wk of freezer storage. Steaks were also evaluated after the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 8 publications
3
36
1
2
Order By: Relevance
“…Surface discoloration ratings paralleled the color desirability scores, with intact muscle steaks having less (P < 0.05) surface discoloration than comminuted structured steaks. Discoloration of structured products has been attributed by several researchers to the addition of NaCl (Ockerman and Organisciak, 1979;Huffman, 1980;Booren et al, 1981b, Chastain et al, 1982, Means and Schmidt, 1986Means et al, 1987). In contrast to our results, Means and Schmidt (1986) and Means et al (1987) observed no deleterious effects on surface discoloration of comminuted structured steaks from the use of an algin/calcium binder.…”
Section: Consumer Evaluationscontrasting
confidence: 86%
“…Surface discoloration ratings paralleled the color desirability scores, with intact muscle steaks having less (P < 0.05) surface discoloration than comminuted structured steaks. Discoloration of structured products has been attributed by several researchers to the addition of NaCl (Ockerman and Organisciak, 1979;Huffman, 1980;Booren et al, 1981b, Chastain et al, 1982, Means and Schmidt, 1986Means et al, 1987). In contrast to our results, Means and Schmidt (1986) and Means et al (1987) observed no deleterious effects on surface discoloration of comminuted structured steaks from the use of an algin/calcium binder.…”
Section: Consumer Evaluationscontrasting
confidence: 86%
“…The efficacy of antioxidant may be in part due to the number of phenolic hydroxyl groups available for free radical scavenging (Rice-Evans, 1996). Chastain et al (1982) studied the effects of BHA, TBHQ and a combination of BHA and TBHQ on restructured combination of beef-pork steaks (50:50). Antioxidants were used at a 0.02% level (based on fat content of meat).…”
Section: Phenolic Antioxidantsmentioning
confidence: 99%
“…Goldman et al (1983) suggested that free radicals produced by lipid oxidation might interact with carotenoid to intensify their oxidation. Use of antioxidants has been attempted for prevention of carotenoid related colour degradation in fi sh, meat and poultry (Green et al 1971, Chastain et al 1982, Li et al 1998). The major cause for carotenoid degradation in foods is oxidation with rates dependent on contact with oxygen, light, heat and presence of pro-and antioxidants (Francis 1985, Haard 1988.…”
Section: Introductionmentioning
confidence: 99%